"Ważniejsze są dla mnie reportaże niż nawet najbardziej sensacyjne korespondencje depeszowe" – rozmowa z Wojciechem Jagielskim o jego reportażach wojennych - Bednarek, Zbigniew (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
Wojciech Jagielski is one of the most outstanding Polish reporters. He is interested in the problems of Central Asia, the Caucasus and Africa. In this interview we can find out what reportage and objectivism mean for him, what the role of the reporter is, what problems he faces, what an ordinary day in an area of war looks like, what arc the stages of work on making a reportage, along with learning about his opinion on contemporary journalism.